Fabrication process of tubes in epoxy resin - Júnior, I. S. M.; Macedo, M. A. (Scientia Plena, 2012)
The manufacturing process of cylindrical tubes, made by mixing epoxy resin with inorganic materials has been studied, producing samples by the method of spillage of the mixture into a mold consisting of two PVC pipes of different diameters. The use of different mold release was evaluated in order to determine what would be the best in your application as well, especially given the ease of removing the sample after curing the composite. The samples produced had a surface with a high degree of polish and your wall devoid of visible defects.